Spherical versus elongated particles – Numerical investigation of mixing characteristics in a gas fluidized bed. (November 2020) - Mema, Ivan; Padding, Johan T.
Highlights: CFD-DEM comparison of mixing characteristics of spherical and elongated particles. Elongated particles show more vigorous mixing compared to spherical particles. Lift force and hydrodynamic torque reduces mixing time for elongated particles. Abstract: The possibility to offer good intermixing between particles is one of the main properties that make fluidized beds such an important industrial appliance. In this work, we use CFD-DEM simulations to compare mixing characteristics of spherical (AR-1) to elongated spherocylindrical particles (AR-4) of aspect ratio In simulation of AR-4 particles, single-particle and multi-particle correlations for hydrodynamic forces are tested. The results show that elongated particles have more vigorous intermixing and lower mixing times compared to spherical particles. Multi-particle correlations have a slight effect on particle mixing, and they increase the difference between AR-1 and AR-4 particles at higher gas velocities. Including hydrodynamic lift force and torque in the case of AR-4 particles leads to more vigorous mixing and lower mixing times.